Serotonergic paraneurones in the female mouse urethral epithelium and their potential role in peripheral sensory information processing. (8th August 2017) - Kullmann, F. A.; Chang, H. H.; Gauthier, C.; McDonnell, B. M.; Yeh, J.‐C.; Clayton, D. R.; Kanai, A. J.; de Groat, W. C.; Apodaca, G. L.; Birder, L. A.
Abstract: Aim: The mechanisms underlying detection and transmission of sensory signals arising from visceral organs, such as the urethra, are poorly understood. Recently, specialized ACh‐expressing cells embedded in the urethral epithelium have been proposed as chemosensory sentinels for detection of bacterial infection. Here, we examined the morphology and potential role in sensory signalling of a different class of specialized cells that express serotonin (5‐HT), termed paraneurones. Methods: Urethrae, dorsal root ganglia neurones and spinal cords were isolated from adult female mice and used for immunohistochemistry and calcium imaging. Visceromotor reflexes (VMRs) were recorded in vivo . Results: We identified two morphologically distinct groups of 5‐HT + cells with distinct regional locations: bipolar‐like cells predominant in the mid‐urethra and multipolar‐like cells predominant in the proximal and distal urethra. Sensory nerve fibres positive for calcitonin gene‐related peptide, substance P, and TRPV1 were found in close proximity to 5‐HT + paraneurones. In vitro 5‐HT (1 μ m ) stimulation of urethral primary afferent neurones, mimicking 5‐HT release from paraneurones, elicited changes in the intracellular calcium concentration ([Ca 2+ ]i ) mediated by 5‐HT2 and 5‐HT3 receptors. Approximately 50% of 5‐HT responding cells also responded to capsaicin with changes in the [Ca 2+ ]i . In vivo intra‐urethral 5‐HT application increased VMRs induced by urethral distention and activated pERK in lumbosacral spinal cord neurones. Conclusion: These morphological and functional findings provide insights into a putative paraneurone‐neural network within the urethra that utilizes 5‐HT signalling, presumably from paraneurones, to modulate primary sensory pathways carrying nociceptive and non‐nociceptive (mechano‐sensitive) information to the central nervous system.